A new two-parameters cubic equation of state with benefits of three-parameters. (16th January 2021) - Kumar, Ashutosh; Upadhyay, Rajeev
Highlights: New format of two-parameters cubic EoS. Reliable density predictions without using volume shift or optimized critical parameters. Reliable phase behavior for pure components and for their mixtures. Volumetric predictions are significantly better and more reliable than that from PR EoS. Computational reliability similar to three-parameters cubi EOS. Abstract: Two-parameters cubic EOSs are not reliable for volumetric predictions. Three-parameters cubic EOSs are not computationally efficient. A new format of two-parameters cubic EoS is presented, which has volumetric predictions similar to that of three-parameters cubic. The proposed EoS has an advantage over the PR-EOS in the compositional phase behavior predictions and is highly reliable for volumetric predictions without the use of either optimized critical parameters or volume-shift parameters. The present form of the two-parameters cubic EoS has AARD<3% for all n-alkanes in comparison to 39% for PR EoS. For other components, the AARD from the present work is 6.5% in comparison to 10.2% from PR EoS. For mixtures also, the present format is found highly reliable with 3.5% AARD for 29 mixtures compared to 10% for PR EoS. Applications, where faster calculations for volumetric as well as compositional phase behavior are required, would greatly benefit from this.